PENGARUH KOMITMEN PROFESIONAL, PERSONAL COST, LOCUS OF CONTROL, SIFAT MACHIAVELLIAN DAN TINGKAT KESERIUSAN KECURANGAN TERHADAP INTENSI UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Kuantan Singingi) - Rifki, Rifki; Hardi, Hardi; Wiguna, Melda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to know the affect of proffesional commitment, personal cost, locus of control, machiavellian, and seriousness of wrongdoing to the internal whistleblowing intentions. The population of this study are employees OPD Kuantan Singingi district as many as 26 OPD. The sample is chosen by purposive sampling method. Through the criteria applied, selected samples of 130 respondents. The analytical method used is multiple linear regression analysis with SPSS application. The result of the research shows that proffesional commitment, personal cost, locus of control, machiavellian, and seriousness of wrongdoing affect internal whistleblowing. The R Square of 0,668 means that the contribution of independent variables (proffesional commitment, personal cost, locus of control, machiavellian, and seriousness of wrongdoing) to the dependent variable internal whistleblowing) is 66,8% while the remaining 33,2% influenced by other variables not included in this study.Keywords : Internal Whistleblowing, professional commitment, personal cost, locus of control, machiavellian, seriousness of wrongdoing